ANALISIS YURIDIS TERHADAP PEMENUHAN HAK SEKSUAL NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS II A BENGKULU BERDASARKAN NATURAL RIGHTS THEORY - Ferawati Royani; Widya Timur; Sandi Apriyanto (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Abstract: The correctional process cannot be separated from its relationship with the respective elements in the correctional system, and also with the whole process in society itself. As creatures of God who in principle need each other, so that humans live in groups and where the law is present to create order and security for the wider community. Crime is an act that violates the rules, a group of people in a semi-closed or semi-open system where most of the interactions are between individuals who are in the group. The formulation of the problem in this study is how the juridical analysis of the fulfillment of the sexual rights of prisoners in the Class II A Bengkulu Penitentiary is based on the Natural Rights Theory. The legal research method used, which is normative-empirical, is basically a combination of normative legal approaches with the addition of various empirical elements, one of the basic needs of prisoners that still escapes the attention of this nation is the biological needs in correctional institutions. Based on the theory of natural rights (natural rights theory), the author analyzes that all humans have the same natural rights, including the fulfillment of sex inmates in prisons. But here the government has not seriously considered the negative impact of the absence of facilities and infrastructure on the fulfillment of sexual rights. If their sexual rights are not fulfilled, the prisoners do deviant things, such as masturbation, same-sex sex and so on.Keywords: Behavior, Sexual Rights, Inmates.